Interactive anticancer effect of nanomicellar curcumin and galbanic acid combination therapy with some common chemotherapeutics in colon carcinoma cells - Arash Jafari; Manouchehr Teymouri; Maryam Ebrahimi Nik; Azam Abbasi; Mehrdad Iranshahi; Mohammad Yahya Hanafi-Bojd; Mahmoud Reza Jafari (Mashhad University of Medical Sciences, 2019)
Objective: In the current investigation, we aimed to study the combined cytotoxicity of curcumin, as a nanomicellar formulation, and galbanic acid (Gal), dissolved in DMSO against the murine C26 and human Caco-2 colon carcinoma cells. Further, curcumin potential for cisplatin and doxorubicin (Dox) co-therapy was studied. Materials and Methods: The combined cytotoxic effect of these phytochemicals at varying dose ratios were examined using the MTT colorimetric assay. Moreover, the time-dependent toxicity of curcumin, cisplatin, Dox, and pegylated liposomal Dox (Doxil) was determined. The interactive anti-proliferative behavior of these compounds was examined using the CompuSyn software. Results: Nanomicellar curcumin showed considerable cytotoxicity in C26 cells 24 hr post-treatment. Co-treatment of cells with curcumin nanomicelles: Gal had a synergistic effect in C26 (at 10:1 molar ratio), and Caco-2 (at 1:5 molar ratio) cell lines in cell cultures. Nanomicellar curcumin showed strong and mild synergistic inhibitory effects in C26 cells when co-administered with Doxil and cisplatin, respectively. Conclusion: Curcumin nanomicelles and Gal had a synergistic effect in C26 and Caco-2 cell lines. It is speculated that nanomicellar curcumin shows synergistic cancer cell killing if administered 24-hr post-injection of Doxil and cisplatin.